Interactive dynamics among therapist interventions, therapeutic alliance and metacognition in the early stages of the psychotherapeutic process†. (2nd January 2019) - Locati, Francesca; Rossi, Germano; Parolin, Laura
Abstract: Objective: Several authors have identified a bidirectional link between patient metacognitive functioning and the therapeutic alliance. Specifically, metacognition might be enhanced by a positive alliance with the clinician, whereas metacognitive deficits might impede the alliance. Interestingly, the therapist's technical interventions might influence both therapeutic alliance and metacognitive functioning. However, little is known about the interactions between these dimensions. The aim of the present study is to explore these interactions more fully in the earliest phase of the therapeutic process.Method: Participants included 24 patients and 12 therapists in training. The Metacognition Assessment Scale-Revised, Collaborative Interaction Scale, and Psychodynamic Intervention Rating Scale were employed in the first three sessions of psychotherapy.Results: Sequential analyses revealed that different therapist interventions co-occurred with three different levels of the therapeutic alliance: A first level characterized by a positive collaboration, a second characterized by a neutral collaboration, and a third characterized by ruptures. Importantly, the patient's metacognitive functioning was found to mediate the relationship between the therapeutic intervention and the therapeutic alliance in the positive and neutral levels of collaboration but not in the ruptures one.Conclusions: These findings suggest that a specific interdependence exists among the therapeutic alliance, technical intervention, and metacognitive functioning.